‘It Ain’t What You Do It’s the Way That You Do It’: Lessons for Health Care From Decommissioning of Older People’s Services - Robinson, Suzanne; Glasby, J.; Allen, K. (Wiley-Blackwell Publishing Ltd., 2013)
Public sector organisations are facing one of the most difficult financial periods in history and local decision-makers are tasked with making tough rationing decisions. Withdrawing or limiting services is an emotive and complex task and something the National Health Service has always found difficult. Over time, local authorities have gained significant experience in the closure of care homes – an equally complex and controversial issue. Drawing on local knowledge and best practice examples, this article highlights lessons and themes identified by those decommissioning care home services. We believe that such lessons are relevant to those making disinvestment decisions across public sector services, including health-care. The study employed semi-structured interviews with 12 Directors of Adult Social Services who had been highlighted nationally as having extensive experience of home closures. Interviews were conducted over a 2-week period in March 2011. Results from the study found that having local policy guidance that is perceived as fair and reasonable was advocated by those involved in home closures. Many local policies had evolved over time and had often been developed following experiences of home closures (both good and bad). Decisions to close care home services require a combination of strong leadership, clear strategic goals, a fair decision-making process, strong evidence of the need for change and good communication, alongside wider stakeholder engagement and support. The current financial challenge means that public sector organisations need to make tough choices on investment and disinvestment decisions. Any such decisions need to be influenced by what we know constitutes best practice. Sharing lessons and experiences within and between sectors could well inform and develop decision-making practices.